Smoke detector using ATMega328 / Mohd Haikal Zainal, Muhamad Arif Yusof and Muhammad Saiful Adli Mohd Othman - Zainal, Mohd Haikal; Yusof, Muhamad Arif; Mohd Othman, Muhammad Saiful Adli (2015)
Due to the dangerous smokes that have been release by several factory without thinking their affect, this project was create to measure the smoke level in the surrounding air. This project presents the design and developments of a prototype smoke detector using ATMega328. This project involves both hardware and software development. This smoke detector is design to educate people on the danger of smoke release in factory. The main component in this project is MQ3 sensor as an input that will detect the level of smoke release in the air. ATMega328 act as a microcontroller for this project. The ATMega328 are programmed to detect the level of smoke in the air using Arduino software. Furthermore, this project also to alert people on how dangerous the smoke release by factory that could harm their health. Finally, the objective is to educate people to take precautions because of the smoke release by factory. The smoke release by the factory will be measure by MQ3 sensor. MQ3 sensor is a gas type sensor which means it will detect gas. If the sensor detect the smoke that has HIGH value, it will show the display on the led screen and the buzzer will be ON. If the sensor detect the smoke that has LOW value, it will also show the display on the led screen and the buzzer will be OFF.